Perkembangan dan Fenomena Rumah Susun Sederhana Sewa (Rusunawa) sebagai Solusi Perumahan Perkotaan Tahun 2000–2020 - Angeli Maharani, Destania; Carolina Santi Muji Utami (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
The objective of this study is to examine changes in public housing policy and to explain why the Simple Rental Apartment Complexes (Rusunawa) in DKI Jakarta became a significant phenomenon in the urban planning of Jakarta in the early 21st century. The methodology employed in this study is a historical research method with a social history approach, which encompasses four stages: heuristics, source criticism, interpretation, and historiography. The results of the study indicate that Rusunawa in DKI Jakarta represent a continuation of the concept of vertical housing dating back to the New Order era, which evolved into an instrument for the redevelopment of slum settlements during the Reform era while also serving as part of the transformation of spatial governance in Jakarta. The study’s conclusions suggest that the construction of Rusunawa tends to prioritize the achievement of physical targets over the socio-economic preparation of residents. Rusunawa have not yet fully met the needs of the low-income population (MBR) as their intended beneficiaries. Keywords: Low-Income Communities (MBR), Public Housing, Rusunawa, Social History, Urban Planning.